SEJARAH MAJELIS SHALAWAT MUHAMMAD RAHMATAN LIL ALAMIN SURABAYA TAHUN 2004-2006 - Zaenalabidin, Ahmad Fauzan (Historia Islamica: Journal of Islamic History and Civilization, 2022)
This study discusses the history and development of the Muhammad Raahmatan Lil Alamin Assembly at Pesapen Surabaya in 2004 – 2016. This research was conducted using historical research methods, which included several steps, namely heuristics, verification, interpretation and historiography. The approach used is a historical approach used to describe past events. While the theory used is the theory of Neil Smelser theory of collective behavior. In this theory it is stated that a group of masses is a group that acts on each other physically and is almost related to the same interests or concerns. From the results of the research that has been done, there are several findings, namely the Shalawat Muhammad Rahmatan Lil Alamin Council was founded in 2004 which was founded by Shaykh Abdul Kahar in Surabaya, Shaykh Abdul Kahar founded the Shalawat Muhammad Rahmatan Lil Alamin Council, he received a mandate from his teacher namely Gus Syamsu Dhuha to spread the practice of Muhammad's blessings to mankind. Shaykh Abdul Kahar began to spread the teachings of Muhammad's blessings in several ways and approaches to several human circles. So that the assembly of shalawat Muhammad rahamatan lil alamin has many followers.